Serangan Penyakit Rebah Kecambah Tanaman Cabai pada Tanah yang Berasal dari Persemaian Tanaman Petani di Lahan Rawa Lebak Kecamatan Pemulutan Kabupaten Ogan Ilir - A Muslim; Suwandi Suwandi; Muhammad Yunus Umar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Muslim et al, 2018. Damping-off of Chili Pepper Growing on Seedbed Soil from Farmers in Swamp Area of Pemulutan, Ogan Ilir. JLSO 7(1):80-87. Research on disease severity of damping-off on chili seedling from used seedbed nursery soil from swampy area land in Pemulutan, Ogan Ilir was conducted in order to know what kind of pathogen that attack chili seddling and how is severe it’s severity. This study was aimed to identify the damping-off pathogens of chili pepper and to measure inoculum potential of seedbed soil from farmers in swamp area of Pemulutan, Ogan Ilir. The experiment was conducted using survey method. The sample was taken by purposive sampling on chili seedbed nursery from six farmers all along swampy area in Pemulutan, Ogan Ilir. The result showed that observation based on the sympton and laboratory assay on damping-off disease infected chili seedling was caused by Rhizoctonia solani. The percentage of Pre-emergence damping-off incidence was ranged from 6.5˗35.5%. The highest Pre-emergence damping-off incidence was observed on soil from Mr. Mimin and lowest incidence was found from Mr. Nukman. The percentage of post-emergence damping-off incidence was ranged from 0.5˗56.5%, where the highest percentage was observed from Mr. Rahmat and the lowest was observed from Mr. Joni. The percentage of disease severity of damping-off was ranged from 0.55˗28.75%, where the highest disease severity was also observed from Mr. Rahmat and the lowest one was observed from Mr. Nukman. Based on disease severity of chili damping˗off observed in this study was high, chili damping˗off disease is important disease during providing seedling. This disease was potential to reduce the quality and quantity of chili production.